Accelerate for Impact Platform (A4IP) 2024 Year In Review - Dowling, Kevin (Bioversity International and International Center for Tropical Agriculture, 2025)
As a catalyst for entrepreneurial scientists, startups, and strategic partners, the CGIAR Accelerate for Impact Platform (A4IP) continued to foster interdisciplinary collaboration across this sector in 2024, bridging research from lab to market for tangible impact in agri-food systems. By co-designing, accelerating, and de-risking the development and deployment of science-based technology-driven solutions for agriculture and climate action, A4IP’s mission is aimed at a healthier, more equitable, and more sustainable future for all.